RESULTS OF CONTINUOUS POSITIVE UPPER AIRWAY PRESSURE TREATMENT IN PATIENTS WITH ATRIAL FIBRILLATION AND OBSTRUCTIVE SLEEP APNEA - A. V. Pevzner; E. Sh. Bayrambekov; A. Yu. Litvin; E. M. Elfimova; V. V. Ermishkin; S. F. Sokolov; S. P. Golitsyn (Российский кардиологический журнал)
Aim. Evaluation of CPAP treatment (continuous positive upper airway pressure) in obstructive sleep apnea patients (OSA) and atrial fibrillation (AF) in comparison with antiarrhythmic medication therapy.Material and methods. Totally, 36 patients included (58% males, mean age 61±11 y.) with AF and definite OSA by the data from cardiorespiratory monitoring. In 6 (17%) patients there was moderate level of respiratory disorders and in 30 (83%) — severe. Twenty four (67%) patients had paroxysmal and 12 (33%) — persistent AF. All patients, to retain sinus rhythm and prevent AF relapses, were taking antiarrhythmic medications (AAM). Therapy by CPAP was recommended to all patients, but after familiarization nights (1-3), 18 agreed to continue this type of treatment at home (group 1), other 18 (group 2) were unable to apply CPAP due to low tolerance. During 12 month follow-up, comparative analysis was done, of AAM efficacy in both groups of patients. Groups did not differ significantly by the medications being taken.Results. With CPAP therapy, in group 1 most patients (12, 67%) during 12 months did not develop AF relapses, and in the group 2 — only 6 (33%) did not have AF. It is worthy to mention than group 1 patients had potentially less chance for antiarrhythmic therapy success, if to consider traditional risk factors of AF, as they had higher body mass (body mass index 39,5 kg/m2 versus 34, p=0,07), more severe sleep respiration disorders (apnea-hypopnea index 50,8 events per hour versus 37,4, p=0,09) and larger left atrium (82 mL versus 60,5, p=0,02) comparing to group 2 patients. During 3-month CPAP treatment, in group 1 patients a significant decrease of P-wave dispersion was noted, by 30,8% (р=0,05).Conclusion. Therapy with CPAP in moderate and severe OSA makes it to more than two times (from 33% to 67%) increase efficacy of antiarrhythmic drug treatment for AF. One of the mechanisms of antiarrhythmic action of CPAP againts AF might be a decrease of atrial conduction time dispersion.